2015
DOI: 10.1016/j.seppur.2015.09.052
|View full text |Cite
|
Sign up to set email alerts
|

Removal of organophosphate esters from municipal secondary effluent by ozone and UV/H2O2 treatments

Abstract: a b s t r a c tOrganophosphate esters (OPEs) have emerged as a new class of contaminants due to their massive use as flame retardants and plasticizers. These contaminants are toxic to aquatic organisms and some of them are not biodegradable in wastewater treatment plants. This study investigated the degradation kinetics of eight typical OPEs during ozone and UV/H 2 O 2 treatments in Milli-Q water, humic acid (HA) solution, and municipal secondary effluent. The studied OPEs included three chlorinated: tris(2-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(27 citation statements)
references
References 31 publications
4
20
0
3
Order By: Relevance
“…From these spectral data, we concluded that TBEP (δ 4.05 ppm) is more susceptible to degradation than TBP and TCEP. This behaviour is in accordance with similar works that reported higher resistance of chlorinated organophosphates esters when they are subjected to advanced oxidation treatments (Yuan et al, 2015).…”
Section: Acute Toxicitysupporting
confidence: 93%
“…From these spectral data, we concluded that TBEP (δ 4.05 ppm) is more susceptible to degradation than TBP and TCEP. This behaviour is in accordance with similar works that reported higher resistance of chlorinated organophosphates esters when they are subjected to advanced oxidation treatments (Yuan et al, 2015).…”
Section: Acute Toxicitysupporting
confidence: 93%
“…Wastewater quality is critical for the performance of AOTs, namely for those here reviewed: For example, a better performance was reported for UV/H2O2 to degrade several organophosphate esters and some of them (chlorinated and one aliphatic) were recalcitrant to ozonation, but the presence of HA improved only the ozonation process, with an opposite trend observed in UV/H2O2 treatment [105]. On the contrary, the same order of degradation rates (UV < UV/H2O2 < Fenton < solar irradiation < photo-Fenton) was observed regardless of the type of WW analysed, in a study comparing the effluents from activated sludge, moving bed bioreactor and coagulationflocculation treatments [20].…”
Section: Future Challenges and Conclusionmentioning
confidence: 92%
“…For ozonation, the following decreasing order of removal was reported: HA solution > UPW > WW effluents. The acidic pH of UPW led to selective ozonation of organic compounds with electron-rich [105] -LP UV lamps (8 W, 26% UVC efficiency) (λmax 254 nm); -H2O2: 20 mg L -1 . functional groups.…”
Section: O3 Uv/h2o2mentioning
confidence: 99%
“…The UV/H 2 O 2 process was the generation of hydroxyl radical (•OH) through the photolysis of H 2 O 2 . The •OH radical was highly reactive and corrodes most of the organic molecules at a very high rate constant [38,39]. Other studies showed that the degradation kinetics of TCPP under visible light irradiation was slower than that under UV-visible irradiation, probably due to the less production of •OH radicals [1,14].…”
Section: Mechanistic Analysis For the Enhancement Of Photodegradationmentioning
confidence: 99%